Respon Kristen Terhadap Kebijakan Asas Tunggal Pancasila Era Orde Baru - Yusup Yusup (Sekolah Tinggi Teologi Syalom Bandar Lampung, 2021)
This study is a comparative study of the response of Christians to political policies. This research specifically explores how the attitude of Christians towards the policy of the Single Principle of Pancasila during the New Order era. Through literature study of primary and secondary sources as well as interviews, this study found that in general there are two attitudes among Christians towards the policy, namely reactive and accommodative. Catholics (MAWI) and Protestants (DGI) reacted reactively to the Single Principles policy, which for them was tantamount to replacing Jesus with Pancasila. Meanwhile, the evangelicals were accommodative by accepting the Pancasila Single Principle policy even before the policy was passed into Law no. 8 of 1985.